Provision of injectable contraceptives by community health workers in sub-Saharan Africa: a systematic review of safety, acceptability and effectiveness - Besong Eric Ayuk; Brenda Mbouamba Yankam; Farrukh Ishaque Saah; Luchuo Engelbert Bain (BMC, 2022)
Abstract Background Injectable contraceptives are the most popular method of contraception in sub-Saharan Africa (SSA), but their availability in clinical settings has been severely limited, despite the scarcity of health care providers and limited access to health facilities. WHO and USAID have endorsed the community-based distribution of injectable contraceptives as a promising option for improving access to family planning services and expanding the method mix for women who want to limit the number of births. Studies have shown that community health workers (CHWs) can provide women with injectable contraceptives that meet acceptable quality standards. The goal of this study is to identify, evaluate and synthesize evidence supporting the use of community-based administration of injectable contraceptives in SSA. Methods This review's guidance was based on a previously developed protocol. Nine international electronic databases and the websites of organizations known to support community-based reproductive health initiatives in SSA were searched systemically. Experts in this area were also contacted for the identification of unpublished literature and ongoing studies. The reference lists of eligible studies were reviewed. The Effective Public Practice Project tool was used to assess the quality and risk of bias in eligible studies. Data were extracted and analysed using a custom data extraction form and a narrative synthesis. Results The search strategy identified a total of 1358 studies with 12 studies meeting the inclusion criteria. One unpublished study was provided by an expert making a total of 13 studies. The results showed that irrespective of the study designs, well-trained CHWs can competently administer injectable contraceptives safely and community-based delivery of injectable contraceptives is acceptable in SSA. Also, the use of community health workers in the provision of depot-medroxyprogesterone acetate expanded access to inhabitants of hard-to-reach areas and led to an overall uptake of injectable contraceptives as well as family planning. Studies that compared CHWs to clinic-based providers revealed equivalent or higher levels of performance in favour of CHWs. Conclusions The CHWs can competently provide injectable contraceptives within SSA communities if appropriately trained and supervised. Hence, SSA policymakers should give this initiative due consideration as a way of improving access to family planning services.